2015
DOI: 10.1021/acsami.5b06833
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Silicon Nitride from Bis(tert-butylamino)silane and N2 Plasma

Abstract: Atomic layer deposition (ALD) of silicon nitride (SiNx) is deemed essential for a variety of applications in nanoelectronics, such as gate spacer layers in transistors. In this work an ALD process using bis(tert-butylamino)silane (BTBAS) and N2 plasma was developed and studied. The process exhibited a wide temperature window starting from room temperature up to 500 °C. The material properties and wet-etch rates were investigated as a function of plasma exposure time, plasma pressure, and substrate table temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
129
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 22 publications
16
129
2
1
Order By: Relevance
“…%. 23 In our case, closer inspection via XPS revealed a relative decrease in the C at. % from 13 at.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…%. 23 In our case, closer inspection via XPS revealed a relative decrease in the C at. % from 13 at.…”
Section: Resultsmentioning
confidence: 48%
“…Film deposition HfN x thin films of $50 nm in thickness were deposited on 100 mm Si(100) substrates with 450 nm SiO 2 using an Oxford Instruments FlexAL ALD reactor, 23,24 equipped with an inductively coupled remote plasma (ICP) source with an alumina dielectric tube. The deposition chamber of the ALD reactor was pumped down by a turbomolecular pump to a base pressure of 1.6 Â 10 À6 Torr before every deposition and thereafter the substrate was transferred to the chamber from the load-lock.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically to address the needs of modern IC and memory processes we have purposely limited substrate temperatures to maximally 350 • C. We have found that across multiple chemistries, different commercial PEALD reactors, and a variety of process conditions, there is a strong correlation between the density of the SiN x films and their WER. In a recent evaluation of PEALD SiN x from BTBAS, 10 the WER and density of thin films was reported. The results presented there follow the correlation presented here well.…”
Section: Discussionmentioning
confidence: 99%
“…10,14,15 To improve thin film properties (crystallinity, morphology, density, trap density) rapid thermal annealing (RTA) is commonly used. However, the thermal budget of RTA should not exceed roughly 400 • C for most IC processes.…”
Section: -2mentioning
confidence: 99%
“…[13][14][15] Previously, plasma annealing or extensions of in-cycle plasma during PEALD have shown similar improvements in thin film properties. 11,16 One of the benefits of ALD is the ability to deposit nanolaminates or composite films of several different materials by utilizing the cyclic nature of the deposition process. Historically this was introduced decades ago for HfO 2 -Ta 2 O 5 dielectric films in electroluminescent displays.…”
Section: Introductionmentioning
confidence: 99%